Children with Language Impairment: Prevalence, Associated Difficulties, and Ethnic Disproportionality in an English Population - Lindsay, Geoff; Strand, Steve (Frontiers in Education, 2016)
Language impairment (LI) is one of the most common types of special educational needs (SENs), not only as a child’s primary need but also as a secondary domain associated with other types of SENs. LI is a risk factor for children’s later development, being associated with enhanced behavioral, emotional, and social difficulties, in particular peer problems and emotional difficulties; literacy difficulties, including both reading and writing; and reduced levels of academic achievement. Risks arising from LI in early childhood may also have an impact through adolescence and into adult life. This study uses national data from the UK government’s annual census of all students aged 5–16 years attending state schools in England at four time periods between 2005 and 2011, over 6 million students at each census. We analyze the data on students with speech, language, and communication needs (SLCN), the Department for Education’s category for students with LI, to examine the overall prevalence of SLCN and the variations in prevalence associated with child factors namely, age, gender, ethnicity, socioeconomic disadvantage, and having English as an additional language, and with contextual factors, namely the school and local authority. We also examine disproportionality of identification of SLCN for different ethnic groups compared with White British children. We discuss the implications of our findings with respect to the current debates regarding the varied terminology for LI, including SLCN, and of a needs-based compared with diagnosis-based approach to assessing and making provision for children and young people with SENs.